2011
DOI: 10.1128/jvi.00335-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Rift Valley Fever Outbreaks in Madagascar Resulting from Virus Introductions from the East African Mainland rather than Enzootic Maintenance

Abstract: Rift Valley fever virus (RVFV),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 23 publications
6
51
0
Order By: Relevance
“…RVF has been endemic in sub-Saharan African countries for more than 80 years and has spread to Egypt, Madagascar, Saudi Arabia, and Yemen (6,7,12,68,71). RVFV causes a high rate of abortion and acute lethal infection in newborn ruminants, such as sheep, goats, and cattle, and febrile illness in humans (13,68,71).…”
mentioning
confidence: 99%
“…RVF has been endemic in sub-Saharan African countries for more than 80 years and has spread to Egypt, Madagascar, Saudi Arabia, and Yemen (6,7,12,68,71). RVFV causes a high rate of abortion and acute lethal infection in newborn ruminants, such as sheep, goats, and cattle, and febrile illness in humans (13,68,71).…”
mentioning
confidence: 99%
“…Reassortment of genome RNA segments by members of the family Bunyaviridae during coinfection has been reported in laboratory-derived and field-isolated viruses (2,8,12,30). Importantly, the absence of p.v.…”
Section: Discussionmentioning
confidence: 99%
“…3 A recent RVF outbreak that occurred in Madagascar was probably associated with infected domestic animals imported from east Africa. 4,5 Another study suggested that this outbreak most likely originated from an endemic cycle localized in southern Madagascar, where virus circulation may occur annually. 6 Although not quantified, it is possible that these two mechanisms co-occur in Madagascar, with a recurrent introduction that helps RVFV maintenance and recirculation in the endemic cycle.…”
Section: Introductionmentioning
confidence: 99%